Exploring the mechanism of action of Sanzi formula in intervening colorectal adenoma by targeting intestinal flora and intestinal metabolism - Shang, Jingyu; Guo, Hong; Li, Jie; Li, Zhongyi; Yan, Zhanpeng; Wei, Lanfu; Hua, Yongzhi; Lin, Lin; Tian, Yaozhou (Frontiers in Microbiology, 2022)
BACKGROUND: Sanzi formula (SZF) is a kind of Chinese herbal compound that has a certain effect on the prevention and treatment of colorectal adenoma (CRA), which can prevent and control the process of colorectal adenoma-cancer transformation. In this study, we explored the mechanism of action of SZF in anti-CRA using 16S rRNA sequencing and metabolomics technology. METHODS: Mice were randomly divided into three groups: Control group, Apcmin/+ model group, and SZF treatment group. Except for the Control group, which used C57BL/6J mice, the remaining two groups used Apcmin/+ mice. The Control group and Apcmin/+ model group were treated with ultrapure water by gavage, while the SZF treatment group was treated with SZF for 12 weeks. During this period, the physical changes of mice in each group were observed. The gut microbiota was determined by high-throughput sequencing of the 16S rRNA gene, and LC-ESI-MS/MS was used for colorectal metabolomics analysis. RESULTS: Sequencing of the 16S rRNA gut flora yielded 10,256 operational taxonomic units (OTUs) and metabolomic analysis obtained a total of 366 differential metabolites. The intestinal flora analysis showed that SZF could improve intestinal flora disorders in Apcmin/+ mice. For instance, beneficial bacteria such as Gastranaerophilales significantly increased and harmful bacteria such as Angelakisella, Dubosiella, Muribaculum, and Erysipelotrichaceae UCG-003 substantially decreased after the SZF intervention. In addition, metabolomic data analysis demonstrated that SZF also improved the colorectal metabolic profile of Apcmin/+ mice. In Apcmin/+ mice, metabolites such as Anserine and Ectoine were typically increased after SZF intervention; in contrast, metabolites such as Taurocholic acid, Taurochenodesoxy-cholic Acid, Hyocholic acid, Cholic acid, and Tauro-alpha-muricholic acid showed noteworthy reductions. Metabolic flora association analysis indicated that 13 differential flora and 11 differential metabolites were associated. CONCLUSION: SZF affects the abundance of specific intestinal flora and regulates intestinal flora disorders, improves colorectal-specific metabolites, and ameliorates intestinal metabolic disorders to prevent and treat CRA. Furthermore, the application of intestinal flora and colorectal metabolomics association analysis offers new strategies to reveal the mechanism of action of herbal medicines for the treatment of intestinal diseases.